Revitalisasi Kurikulum Merdeka di SDN Semangat Dalam 3 Banjarmasin - Maulida, Ridhna; Ruhama, Algina; Hidayah, Nurul; Novaliana, Salsabilla; Pratiwi, Diani Ayu (ARZUSIN, 2025)
This study is motivated by the limited research on the revitalization of the Merdeka Curriculum, despite its significant impact on improving the quality of education at SDN Semangat Dalam 3 Banjarmasin. The study aims to explore the implementation of the Merdeka Curriculum revitalization and identify supporting factors and challenges. The research adopts a qualitative descriptive case study design, with a sample of one principal and one teacher selected through purposive sampling. Data was collected using in-depth interviews, classroom observations, and curriculum document analysis, and analyzed through thematic analysis. The findings reveal that the revitalization of the Merdeka Curriculum has enhanced instructional innovation and fostered active involvement of teachers and students in learning. The principal applied a transformational leadership style to motivate teachers, while teachers assumed the role of facilitators in active learning. The establishment of teacher learning communities also contributed to the successful implementation of the curriculum. These findings align with organizational change theory in education, which emphasizes collective leadership and collaboration, as well as transformational leadership theory, which views school principals as change agents. The role of teachers as facilitators aligns with constructivist learning theory, which emphasizes student-centered learning. The study concludes that the success of Merdeka Curriculum revitalization is influenced by synergy between principals and teachers. The implications include theoretical contributions by enriching the literature on Merdeka Curriculum implementation, and practical recommendations for education authorities and schools to enhance teacher training, leadership, and sustainable teacher learning communities. Future research focuses on the long-term impact of curriculum revitalization on student outcomes.